Branding in Global Marketing Management - Dotsenko, G.V.; Tsysaruk, S.S. (Економічний вісник Донбасу, 2013)
This article describes the essence of branding; it explains what identifies the brand equity and why do some companies prefer to have a locally based brand to a globally based brand. This work clarifies the meaning of a brand extension and brand dilution, and highlights the examples of the most developed brands. The purpose of this paper is to provide the reader with the information about the brands and to identify factors that affect the success of the brand development. У статті описано сутність брендінгу; пояснюється, що визначає гідність марки і чому деякі компанії воліють мати бренд на місцевому рівні, ніж на глобальному рівні. Автор пояснює необхідність розширення і розведення бренду, а також показує приклади з найбільш розвинених брендів. Метою цієї статті є інформувати читача про бренди та визначити фактори, які впливають на успішний його розвиток. В статье описывается суть брендинга; объясняется, что определяет достоинство марки и почему некоторые компании предпочитают иметь бренд на местном уровне, чем на глобальном уровне. Автор поясняет суть расширения и разведение бренда, а также показывает примеры из наиболее развитых брендов. Целью этой статьи является информирование читателя о брендах и определить факторы, которые влияют на успешное его развитие.